Alienation and Intimacy: A Study of Female Body Perception, Management and Transformation in Assisted Reproduction - Tingting XI; Zhizhong WANG; Shangman YAO (Yixue yu zhexue, 2025)
Alienation and intimacy provide a unique perspective to explore women's bodily experiences in assisted reproduction. While assisted reproductive technologies bring hope for motherhood to women experiencing infertility, they also subject them to multiple forms of alienation, including the separation between a healthy body and a diseased body, between the role of motherhood and reproductive ability, and between technological interventions and social relationships. However, women actively respond to alienation through actions such as health management and proactive learning. Through these practices, they gradually bridge the sense of alienation, leading to transformations in their biological body, social body, and cognitive perceptions. In doing so, they rebuild connections with themselves and with society, achieving a transformation from alienation to intimacy.